Impact of GHRM on Organizational Performance: Analyzing the Mediating Role of Green Innovation and moderating Role of Green Strategy in the Relationship between GHRM and Organizational Development (Journal of Asian Development Studies, 2025)
This study examines the relationship between Green Human Resource Management (GHRM) practices and organisational performance, with a focus on the role of green innovation and green strategy in shaping this relationship. Data were gathered from 400 employees serving in 14 prominent manufacturing firms in Pakistan. The analysis employed structural modelling techniques, incorporating mediation and moderation variables, to diagnose their role in the relationship between GHRM and organisational performance. The findings reveal that GHRM has a strong and positive impact on organisational performance. Moreover, the results highlight that green innovation acts as a significant mediating channel, while the existence of a well-defined green strategy serves to fortify this relationship as a moderator. The findings provide empirical support for the Resource-Based View (RBV) theory by establishing that human capital represents a significant intangible resource, and they also strengthen the Natural Resource-Based View (NRBV) by demonstrating that integrating ecological strategies with innovation enhances the effectiveness of HRM practices. Collectively, the study underscores the importance of aligning GHRM with ecological objectives and innovative capability to achieve sustainable organisational performance.